Effect of non-uniformity on concentrator multi-junction solar cells equipped with refractive secondary optics under shading conditions. (1st January 2022) - Saura, José M.; Chemisana, Daniel; Rodrigo, Pedro M.; Almonacid, Florencia M.; Fernández, Eduardo F.
Abstract: Non-uniformity is a relevant concern of concentrator photovoltaic systems (CPV) due to its impact on the performance of multi-junction (MJ) solar cells. This work is focused on a state-of-the-art investigation related to the effects of shading on the irradiance profiles and electrical performance of MJ cells. For doing this, three different CPV single-units with a concentration of ≈559x have been experimentally investigated indoors at the CPV laboratory of the University of Jaén. The units are made up of poly(methyl methacrylate) (PMMA) Fresnel lens and standard GaInP/GaInAs/Ge MJ cells. Also, single-lens-optical element (SILO-Pyramid) and refractive truncated pyramid (RTP) homogenizers have been considered. The results indicate that shading produces additional spatial and spectral non-uniformities, and that these are reduced by the use of homogenizers. In addition, the non-uniform spectral illumination has been identified as the main cause of the additional reduction of the performance of MJ solar cells. In this sense, the SILO-Pyramid provides the best results and shows a significantly stable spectral performance under shading conditions. For a no-homogenizer case, the maximum power shows a reduction of 86.3% for a shading factor of 80%, while it is only reduced by 83.2% and by 81.6%, respectively, for the RTP and SILO-Pyramid. Highlights: Non-uniformity on multi-junction solar cell caused by shading is investigated. Different types of refractive homogenizers are considered. Shading is produced on the surface of a Fresnel lens by using opaque masks. Electrical measurements and charge-coupled device camera photographs are used. Results will help to propose strategies to mitigate non-uniformities under shading.